2021
DOI: 10.1080/21655979.2021.1971482
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of PRKCA/PRKCA-AS1 interplay facilitates DNA methyltransferase 1 recruitment on DNA methylation to affect protein kinase C alpha transcription in mitral valve of rheumatic heart disease

Abstract: In the present study, mitral valve tissues from three mitral stenosis patients with RHD by valve replacement and two healthy donors were harvested and conducted DNA methylation signature on PRKCA by MeDIP-qPCR. The presence of hypomethylated CpG islands at promoter and 5ʹ terminal of PRKCA was observed in RHD accompanied with highly expressed PRKCA and downregulated antisense long non-coding RNA (lncRNA) PRKCA-AS1 compared to health control. Furthermore, the enrichments of DNMT1/3A/3B on PRKCA were detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The mechanism behind the opposite effects on tumor of NEAT1.1 and NEAT1.2 still remain obscure [13]. According to previous studies of the same kind non-coding RNAs in nucleus [14,15], lncRNA could facilitate the connection between transcription factors or epigenetic regulators and DNA elements. In our research, our data unexpectedly supports that a large number of nucleus-expressed RNAs are enriched on NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the opposite effects on tumor of NEAT1.1 and NEAT1.2 still remain obscure [13]. According to previous studies of the same kind non-coding RNAs in nucleus [14,15], lncRNA could facilitate the connection between transcription factors or epigenetic regulators and DNA elements. In our research, our data unexpectedly supports that a large number of nucleus-expressed RNAs are enriched on NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Santos-Bezerra et al investigated the risk associated with DNMT1 mutations in diabetes and found that the DNMT1 SNP rs11085721 was associated with a risk of cardiovascular autonomic neuropathy in females with type I diabetes [140]. Lastly, downregulated lncRNA, protein kinase C alpha antisense RNA 1 (PRKCA-AS1) decreases DNMT1-mediated methylation (Figure 5) of the promoter region of protein kinase C alpha (PRKCA), and subsequently increases PRKCA expression in the mitral valves of patients with rheumatic heart disease, suggesting a DNMT-regulated mechanism in valvular heart disease [141].…”
Section: Dnmts In Other Cardiac Disordersmentioning
confidence: 99%